2022
DOI: 10.3389/fnagi.2022.780817
|View full text |Cite
|
Sign up to set email alerts
|

Sharpening Working Memory With Real-Time Electrophysiological Brain Signals: Which Neurofeedback Paradigms Work?

Abstract: Growing evidence supports the idea that the ultimate biofeedback is to reward sensory pleasure (e.g., enhanced visual clarity) in real-time to neural circuits that are associated with a desired performance, such as excellent memory retrieval. Neurofeedback is biofeedback that uses real-time sensory reward to brain activity associated with a certain performance (e.g., accurate and fast recall). Working memory is a key component of human intelligence. The challenges are in our current limited understanding of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 148 publications
(136 reference statements)
0
11
0
Order By: Relevance
“…For instance, the alpha band (7)(8)(9)(10)(11)(12)(13), primarily observed in posterior brain regions, is associated with relaxed wakefulness, and a decrease in alpha activity is linked to improved concentration and sustained attention [12]. The sensorimotor rhythm (SMR), a sub-band of the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and found as oscillations between 12 and 15 Hz over the sensorimotor cortex, is also associated with attention, with its upregulation frequently targeted [13]. Additionally, the theta band (5-7 Hz) is frequently used in NFB training due to its association with memory [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the alpha band (7)(8)(9)(10)(11)(12)(13), primarily observed in posterior brain regions, is associated with relaxed wakefulness, and a decrease in alpha activity is linked to improved concentration and sustained attention [12]. The sensorimotor rhythm (SMR), a sub-band of the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and found as oscillations between 12 and 15 Hz over the sensorimotor cortex, is also associated with attention, with its upregulation frequently targeted [13]. Additionally, the theta band (5-7 Hz) is frequently used in NFB training due to its association with memory [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies targeting these frequency bands in EEG-NFB have shown promising effects on cognitive processes in both healthy young and elderly adults, as well as individuals with mild cognitive impairment and dementia. Typically, NFB training involves 5 to 30 sessions, lasting 10 to 90 min each, and is conducted weekly or several times a week [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical trial reported a positive effect of theta-down NFB on learning memory and overall cognitive performance in patients with Alzheimer’s disease [ 14 ]. Several systemic reviews provided evidence of NFB in the elderly [ 15 , 16 , 17 ]. Jiang et al [ 15 ] reviewed 13 clinical trials of NFB on working memory function in elderly people (including healthy, MCI, and stroke), and 11 trials reported positive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Several systemic reviews provided evidence of NFB in the elderly [ 15 , 16 , 17 ]. Jiang et al [ 15 ] reviewed 13 clinical trials of NFB on working memory function in elderly people (including healthy, MCI, and stroke), and 11 trials reported positive findings. Laborda–Sánchez et al [ 16 ] reviewed 14 clinical trials of NFB on aging-associated cognitive decline, and they reported that NFB improved memory in healthy and unhealthy participants, mainly when the theta waves and SMR were trained.…”
Section: Introductionmentioning
confidence: 99%
“…In the cerebral cortex, MI and motor execution of the same action have similar activity patterns. The goal of motor-imagery BCIs (MI-BCIs) is to control an external object by inducing and modulating the brainwaves of interest during the training sessions so that the BCI system can determine the user's intention in real-time in testing sessions (Jiang et al, 2022 ). Several studies have explored the influences of aging on different aspects of MI, such as vividness (Malouin et al, 2010 ), working memory (Schotta, 2012 ), and the temporal performance of the MI (Personnier et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%